SIKAP MASYARAKAT TERHADAP ALIH FUNGSI LAHAN RUANG TERBUKA HIJAU (RTH) MENJADI AREAL PERTAMBANGAN BATU - Tsabita Naqiyya; Hari Kaskoyo; Rommy Qurniati (Lambung Mangkurat University-Indonesia, 2020)
Global warming is a problem that must be faced by living things. To reduce global warming by providing Green Open Space (GOS). GOS in the city of Bandar Lampung has experienced a broad decline due to the rampant land conversion as happened at Bukit Sukamenanti, due to the existence of rock mining. The purpose of this study was to determine the attitudes of the community, the relationship between the level of knowledge and attitudes and willingness to pay the community to maintain open green space. The sampling method used was simple random sampling with a total of 93 respondents consisting of 35 miners and 58 non-miners. Data collection uses observation, interview and literature studies. Data analysis using quantitative descriptive analysis techniques. The results of the study is the attitude of the community refused to change land use as much as 66.5%. The level of knowledge has a very significant positive relationship to the attitude of the non mining community, but has a non-significant negative relationship between the level of knowledge and the attitude of the mining community. The higher the level of knowledge the community is not the miner, the more positive his attitude will be. But for the mining community, even though they have a high level of knowledge, they do not have an influence on attitudes because of the economic needs that must be met from mining. Total value of willingness to pay the community to maintain green open space is IDR 89.185.648/month.